A small-scale realistic inter-laboratory accident dosimetry comparison using the TL/OSL from mobile phone components. (January 2022) - Kim, Hyoungtaek; Yu, Hyungjoon; Discher, Michael; Kim, Min Chae; Choi, Yoomi; Lee, Hyunseok; Lee, Jeong Tae; Lee, Hanjin; Kim, Young-su; Kim, Han Sung; Lee, Jungil
Abstract: An inter-laboratory comparison of a small-scale field experiment was conducted in the framework of the Korea retrospective dosimetry network (KREDOS) to verify the reliability and compatibility of thermoluminescence and optically stimulated luminescence techniques for accident dosimetry. Three institutes participated in this comparison, including the Korea Atomic Energy Research Institute, the Korea Institute of Nuclear Safety and the University of Salzburg. Two adult CIRS torso phantoms were used as virtual subjects exposed to a high-activity Ir-192 source, developing both homogeneous and inhomogeneous exposures in a shielded enclosure. The target materials for dose estimation were mobile phone components, such as resistors, display glasses, and chip cards. LiF:Mg, Cu, Si thermoluminescent (TL) detectors were used as reference dosimeters. The mobile phones were attached to the chest, hip, and thighs of the anthropomorphic phantoms. The measured doses ranged from 100 mGy to 2 Gy, depending on the position of the mobile phone on the phantom. The proficiency of the dose assessment was tested at three laboratories. Using the applied protocols, the local dose distribution on the display glasses was unclear, but the distribution around the body was confirmed. Highlights: TL/OSL dosimetry techniques using mobile phone components have been applied to a realistic radiological accident. Inter-laboratory comparison results have shown a good agreement between the institutes and materials. Dose distributions around the anthropomorphic phantoms have been confirmed.